Perkahwinan campur dan hubungannya dengan kebahagiaan keluarga: Kajian di Selangor / Nurzahidah Jaapar - Nurzahidah , Jaapar (2011)
With the increasing foreign immigrant rate and multicultural in Malaysia it seems inevitable that there will be a corresponding increase in mixed marriages practice in Malaysia. Even though, this group is still small in number, however some of our local societies are keen to choose partner outside from the similar distinctive circle such as different races and citizenship. Still, this phenomenon not exempted from several disputable issues especially on the quality of marriage among couple intermarries. Thus, the aim of this study was to identify the effect of mixed marriage and its correlation with family happiness in Selangor Darul Ehsan. Both library research and interview methodology were utilised in this study. The interview method consisted of semi-structural interview and in-depth interview. The information was gathered with the aid of an interview questions. Eight respondents were asked from four main zones in Selangor specifically the mixed marriage spouse who lived in Selangor. The result of this study revealed that all respondent indicated a high level of satisfaction with their marriage. Overall this study was point out that all respondent has implementing all important elements in obtaining a happy family from Islamic point of view. It is hoped that, this discussion and explanation presented will benefit particularly to Muslim intermarriage.